2022
DOI: 10.1590/fst.84622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phospholipid type and concentration on the emulsion stability and in vitro digestion behaviors of fish oil-loaded emulsions

Abstract: Phospholipid (PL) have favorable emulsification ability. The simultaneous application of PL and protein is one of the research hotspots. In this work, the impact of egg yolk PL (EPL), soyabean PL (SPL) and their concentrations on the fish oil-loaded PL/gelatin (GTN)-stabilized emulsions were studied. The results suggested that SPL/GTN-stabilized emulsions comprised bimodal of droplets, and monomodal was observed in EPL/GTN, and GTN-stabilized emulsions. The related droplet sizes were as follows: 1.5% EPL/GTN <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Nduka et al [29] have suggested that the significant differences in specific gravity between PSO and PO appear to be attributed to their distinct structural compositions. Phospholipids play important roles in the structure and function of cell membrane, act as emulsifiers in food production, and have antioxidant activities [30]. Moreover, the phospholipid content of crude oil has been established to be a key factor influencing oil quality, emulsion gel formation stability, and melting point.…”
Section: Resultsmentioning
confidence: 99%
“…Nduka et al [29] have suggested that the significant differences in specific gravity between PSO and PO appear to be attributed to their distinct structural compositions. Phospholipids play important roles in the structure and function of cell membrane, act as emulsifiers in food production, and have antioxidant activities [30]. Moreover, the phospholipid content of crude oil has been established to be a key factor influencing oil quality, emulsion gel formation stability, and melting point.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have addressed lipid oxidation and hydrolysis. Fish and other aquatic products are widely used in experimental studies because of large amounts of polyunsaturated fatty acids that are easily oxidized to lower fatty acids, aldehydes, and ketones (Araújo et al, 2022;Yin et al, 2022), lipid oxidation product-protein interactions that lead to changes in the functional structure of proteins, resulting in deterioration of flavor, color, and texture.…”
Section: Lipid Oxidationmentioning
confidence: 99%